Efficacy and Safety of Complete Endoscopic Resection of Colorectal Neoplasia Using a Stepwise Endoscopic Protocol with SOUTEN, a Novel Multifunctional Snare - Shinji Yoshii; Marina Kubo; Mio Matsumoto; Takefumi Kikuchi; Yasunari Takakuwa (Korean Society of Gastrointestinal Endoscopy, 2020)
Background/Aims A multifunctional snare SOUTEN has a sharp tip at the top of the snare loop that enables incision of the mucosa, dissection of the submucosal layer, and snaring of lesion. This study assessed the efficacy and safety of complete endoscopic resection of colorectal neoplasia using SOUTEN. Methods We analyzed the rates of gross en bloc resection and complete resections of 108 consecutive tumors from 69 patients resected by precutting endoscopic mucosal resection (precutting), hybrid endoscopic submucosal dissection (hybrid), or conventional endoscopic submucosal dissection (conventional) using SOUTEN. Results Out of the 108 tumors, 50 were resected by precutting, 27 were resected by hybrid after attempting precutting, and the remaining 31 were resected by conventional after attempting precutting and hybrid resections. The median tumor sizes were 14.5 mm for precutting, 16.4 mm for hybrid, and 21.1 mm for conventional. The success rate of gross en bloc resection and histological complete resection were 100% and 94.0% for precutting, 96.4% and 96.4% for hybrid, and 100% and 100% for conventional method, respectively. No procedure-related complication occurred. Conclusions By using SOUTEN, precutting and hybrid were successfully performed on 10-30 mm tumors with a shorter procedure time than conventional without major complications.